Articulations between psychoanalysis and literature from the book “Livro sobre nada” by Manoel de Barros (Research, Society and Development, 2023)
This research seeks to carry out a study on possible articulations between psychoanalysis and literature based on the work “Livro sobre nada” by Manoel de Barros. The development of the work will be divided into 3 topics. In the first the objective is to relate art and psychoanalysis. In the second, it is proposed to discuss some psychoanalytic concepts of Sigmund Freud and Jacques Lacan, such as the unconscious and language, using the poems of Manoel de Barros as exemplification and basis. And in the third and final topic, the relationship and rapprochement between the artistic act and the analytical act will be discussed, with the poems of Manoel de Barros. To this end, the bibliographical research method was used, through the works of Freud, Lacan, commentators on these main authors of psychoanalysis, and Google Scholar and LILACS databases, with the keywords “Psychoanalysis”, “Psychoanalysis in extension ”, “Literature”, “Art”, “Poetry” and “Manoel de Barros”. It was possible to relate the chosen poems, covering the concepts of unconscious, temporality, knowledge and language, as well as establishing connections between the act of creation and the analytical act with poetry. It was concluded that poetry and literature play significant roles in the history of psychoanalysis and the contemporary construction of psychoanalytic theory, and that analysts can use Manoel de Barros' poetry to enrich their practices and productions in the field of psychoanalysis.